Osteoprotegerin and cardiovascular mortality in patients with non-ST elevation acute coronary syndromes. Issue 10 (28th February 2012) - Røysland, Ragnhild; Bonaca, Marc P; Omland, Torbjørn; Sabatine, Marc; Murphy, Sabina A; Scirica, Benjamin M; Bjerre, Mette; Flyvbjerg, Allan; Braunwald, Eugene; Morrow, David A
Abstract : Objective: To assess the relationship between osteoprotegerin (OPG) and cardiovascular death, and the pathobiological mechanisms contributing to the association, in acute coronary syndromes (ACS). Design: Prospective observational. Setting: Biomarker substudy of MERLIN-TIMI 36, a randomised, placebo controlled trial of ranolazine in non-ST elevation (NSTE)-ACS. Patients: 4463 patients with NSTE-ACS. Interventions: Ranolazine or placebo. Main outcome measures: Incidence of cardiovascular death (CV death); additionally, heart failure (HF), cardiac arrhythmias, inhospital ischaemia, severe recurrent ischaemia or recurrent myocardial infarction (MI). Results: During a median follow-up of 341 days, 208 patients died of cardiovascular causes. The OPG baseline concentration was strongly associated with both 30 day and 1 year incidence of CV death. After adjustment for conventional risk markers, OPG concentrations (log transformed) remained a significant predictor of CV death by 30 days (HR (95% CI) 2.32 (1.30 to 4.17); p=0.005) and by 1 year (HR 1.85 (1.33 to 2.59); p<0.001). Baseline levels of OPG were also an independent predictor of new or worsening HF at 30 days (HR 2.25 (1.38 to 3.69); p=0.001) and 1 year (HR 1.81 (1.26 to 2.58) p=0.001). By univariable analysis, higher OPG was associated with both early ischaemic and arrhythmic events. Although OPG levels were associated with recurrent MI within 12 months, this association was attenuated and no longer significant after multivariable adjustment. Conclusions: OPG is independently associated with 30 day and 1 year risk of cardiovascular mortality and HF development after NSTE-ACS. As no independent relationship between OPG levels and recurrent ischaemia or MI was observed, myocardial dysfunction may be a more important stimulus for OPG production than ischaemia in ACS.